Yeast growth plasticity is regulated by environment-specific Multi-QTL interactions - Bhatia, Aatish; Yadav, Anupama; Zhu, Chenchen; Gagneur, Julien; Radhakrishnan, Aparna; Steinmetz, Lars M.; Bhanot, Gyan; Sinha, Himanshu (G3: Genes|Genomes|Genetics, 2014)
For a unicellular, non-motile organism like Saccharomyces cerevisiae, carbon sources act both as nutrients and as signaling molecules and consequently affect various fitness parameters including growth. It is therefore advantageous for yeast strains to adapt their growth to carbon source variation. The ability of a given genotype to manifest different phenotypes in varying environments is known as phenotypic plasticity. To identify quantitative trait loci (QTL) that drive plasticity in growth, two growth parameters (growth rate and biomass) were measured in a published dataset from meiotic recombinants of two genetically divergent yeast strains grown in different carbon sources. To identify QTL contributing to plasticity across pairs of environments, gene-environment interaction mapping was performed, which identified several QTL that have a differential effect across environments, some of which act antagonistically across pairs of environments. Multi-QTL analysis identified loci interacting with previously known growth affecting QTL as well as novel two-QTL interactions that affect growth. A QTL that had no significant independent effect was found to alter growth rate and biomass for several carbon sources through two-QTL interactions. Our study demonstrates that environment-specific epistatic interactions contribute to the growth plasticity in yeast. We propose that a targeted scan for epistatic interactions, such as the one described here, can help unravel mechanisms regulating phenotypic plasticity. © 2014 Bhatia et al.
CRIS-Team Scopus Importer:2023-03-11
Keywords: Carbon source; Gene-environment; Gene-gene; Growth plasticity; Interaction; Locus; Quantitative trait; Variation